2023
DOI: 10.3390/catal13010163
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of CuO-TiO2 Nanoparticles for the Degradation of Organic Pollutants: Physical, Optical and Electrochemical Properties

Abstract: CuO-TiO2 nanocomposites were successfully synthesized using the C. benghalensis plant extracts. The effect of the composition of CuO to TiO2 on the morphological, optical, electrochemical, and photodegradation efficiency in the composites was studied. SEM, XRD, UV-vis, FTIR, TGA, BET, and CV were used to characterize these materials. The XRD data reported the tenorite structure of the CuO and the anatase phase of the TiO2. SEM showed the spherical morphologies for all the CuO-TiO2 NPs, and these were also meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…57 The peak at 1055 cm −1 is related to OH vibrations. 55,56 On the basis of the reported results, we can assume that the peaks at 768, 655 and 420 cm −1 correspond to Ti-O and O-Ti-O vibrations, and the peaks at 580, 490 cm −1 correspond to Cu-O vibrations.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…57 The peak at 1055 cm −1 is related to OH vibrations. 55,56 On the basis of the reported results, we can assume that the peaks at 768, 655 and 420 cm −1 correspond to Ti-O and O-Ti-O vibrations, and the peaks at 580, 490 cm −1 correspond to Cu-O vibrations.…”
Section: Resultsmentioning
confidence: 84%
“…Two new absorption bands had appeared at 580, 490 cm −1 for TiO 2 /Cu x O. It was reported that 53,[55][56][57] Meanwhile, Cu-Ti vibrations are located at 540 cm −1 . 57 The peak at 1055 cm −1 is related to OH vibrations.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have reported an absorbance band at 379 nm, corresponding to the ZnO absorption peak, and the Ag NPs peak at 402 nm [58]. The corresponding bandgap for 1% Ag-ZnO-CSs was determined to be 3.75 eV by extrapolating the linear region of Tauc's plot [62]. This value is slightly higher than the 3.33 eV bandgap reported by Kotlhao et al [59].…”
Section: Optical Propertiesmentioning
confidence: 73%
“…But, the required Zanthoxylum armatum mediated ZnO catalyst's dose is six times higher and comparative dye concentration is also smaller. On the other hand, PN/ZnO has also improved degradation efficiency as compared to other green-derived metal oxides acting as photocatalysts, which have extended time periods but the degradation is still not impressive [117][118][119][120]. Consequently, the present PN/ZnO photocatalyst emerges as a promising candidate, showcasing superior performance in the realm of photocatalysis.…”
Section: Investigation Of Photodegradation Kinetics Via Pseudo-order ...mentioning
confidence: 94%